Wireless Controlling for Garbage Robot (G-Bot) - Nyayu Latifah Husni; Robi Robi; Ekawati Prihatini; Ade Silvia Handayani; Sabilal Rasyad; Firdaus Firdaus (Computer Engineering and Applications Journal, 2021)
This paper presents one of the solutions in overcoming the garbage problems. The people sometimes feel too lazy to throw the garbage into proper place due to their habit that has been grown since little kids. In this research, A G-Bot, a robot that has function as the garbage container is offered. By using an Internet of Things (IoT) application, the users can control the motion of the G-Bot wirelessly, so that it can move to the users’ desired location. In addition, the covers of the G-Bot can also be opened using smart phones that connected to the G-Bot. A Blynk that acts as the IoT Application is used in order to set up the G-Bot communication. From the experimental result, it can be concluded that the proposed research has been successful to be implemented. The users can move the G-Bot to the targeted location wirelessly, and they can also open and close the G-Bot’s lids wirelessly trough the mobile phones.